ADDRESSING ISLAMIC ECONOMIC LAWSUIT ON RELIGIOUS COURTS AND FINANCIAL INSTITUTIONS OF CENTRAL KALIMANTAN - Muhammad Luthfi Setiarno Putera; Muhammad Amin; Reza Noor Ihsan; Muhammad Faqihuddin Ibnu Sabil (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
The development of sharia financial institutions which continues to experience a positive trend in Central Kalimantan does not rule out the possibility of sharia economic disputes to emerge. Thus, there needs to be further elaboration regarding the potential and prospects for sharia economic disputes in Central Kalimantan and how prepared sharia financial institutions and religious courts are in handling sharia economic cases. This research is a type of empirical juridical research with a case approach which relies on primary data sources obtained directly from the field using observation, interviews and documentation methods which are then analyzed using analytical descriptive methods. The results of the research led the author to the first conclusion, that the potential/prospects for sharia economic matters in Central Kalimantan were very large, this could not be separated from the existence of sharia financial institutions which could serve users in various levels of society, both upper-middle and lower-middle class. Second, the readiness of Islamic financial institutions to address Islamic economic issues is supported by a sound management system. The principle of